When online learning becomes compulsory: Student nurses' adoption of information communication technology in a private nursing education institution - Petra Bester; Karlien Smit; Maryke de Beer; Pieter H. Myburgh (AOSIS, 2021)
Background: Integrating the use of information communication technology (ICT) in nursing curricula when preparing student nurses for the digital health future such as the sudden online learning as a result of the coronavirus disease 2019 (COVID-19) pandemic is vital. However, when student nurses in a South African private nursing education institution, struggled to complete obligatory online learning courses, nurse educators had to search for solutions. Objectives: To explore the barriers and enablers for ICT adoption by a diverse group of student nurses in a private nursing education institution in the Free State Province. Method: Following a qualitative, explorative, interpretive-descriptive design, student nurses were invited to participate. Based on all-inclusive, purposive sampling with inclusion criteria enabled selecting, a total of 17 participants who took part in three focus groups and written narratives. Transcribed interviews underwent thematic analysis with co-coder consensus. The study adhered to strategies to enhance trustworthiness. Results: Students shared their views related to ICT and online learning within their theory and practice training. Student nurses held positive, negative and contrasting views of ICT adoption and online learning. Actions to master ICT adoption and online learning are highlighted. Information communication technology brings a challenging interdependence between nurses and technology. Conclusion: Integration of ICT into nursing programmes is important. The enablers and barriers to ICT are described. Expose students to different technologies, especially using smart phones to search for (academic/non-academic) information. The adoption of ICT should enhance the learning process and facilitate deep learning. Students preferred online learning for self-assessment and described how they tried to master ICT and online learning. Information communication technologies in the clinical setting highlight the challenged interdependence between nurses and technology. Context-specific recommendations are proposed.